Cardiovascular Disease Outcomes Associated with Three Major Inflammatory Dermatologic Diseases: A Propensity-Matched Case Control Study. Issue 4 (December 2016) - Marshall, Vincent; Moustafa, Farah; Hawkins, Spencer; Balkrishnan, Rajesh; Feldman, Steven
Abstract Introduction Inflammation is an established component of cardiovascular disease (CVD) and an underlying factor of several dermatologic conditions including rosacea, atopic dermatitis, and psoriasis. Identifying potential associations between these dermatologic and cardiovascular diseases can better inform holistic healthcare approaches. The objective of this study was to determine whether rosacea, psoriasis or atopic dermatitis are independent risk factors for CVD 1 year following diagnosis. Methods Using a large commercial claims database of 21, 801, 147 lives, we employed a propensity-matched logistic regression to evaluate the association between diagnoses of rosacea, psoriasis, or atopic dermatitis and a 1-year risk of being diagnosed with cardiovascular disease. Control patients were matched based on health-care utilization, age and overall health status as defined by a modified Deyo–Charlson comorbidity index. Results The analysis included 2105 rosacea, 622 atopic dermatitis, 1536 psoriasis, and 4263 control patients. Compared to propensity-matched controls, the adjusted odds of cardiovascular disease were not higher in patients with rosacea (odds ratio: 0.894, p  = 0.2713), atopic dermatitis (OR 1.032, p  = 0.8489), or psoriasis (OR 1.087, p  = 0.4210). In univariate analysis, the unadjusted odds of cardiovascular disease was higher in patients with psoriasis (OR 1.223, p  = 0.0347). Conclusions Limitations of this study include the short follow-up period and inclusion of only commercially insured patients limit the generalizability of these findings. In this large study of patients with rosacea, atopic dermatitis, and psoriasis, we did not detect an increased 1-year risk of cardiovascular disease after adjusting for confounders.